Crosstalk Analysis of Heterogeneous Multicore Fibers Using Coupled-Mode Theory - Takeshi Fujisawa; Yoshimichi Amma; Yusuke Sasaki; Shoichiro Matsuo; Kazuhiko Aikawa; Kunimasa Saitoh; Masanori Koshiba (IEEE Photonics Journal)
Intercore crosstalk of heterogeneous multicore fiber is investigated based on coupled-mode theory. Random twisting model is used for estimating the crosstalk. The crosstalk of two kinds of fibers: triangular lattice 30-core fiber with four kinds of cores and square lattice 32-core fiber with two kinds of cores is investigated both theoretically and experimentally. Unlike previous study, measured crosstalk for all the combinations of cores for both fibers is in good agreement with calculated values with single correlation length, showing the validity of the theoretical model used here.